Introduction to the Soil carbon sequestration in the Nationally Determined Contributions webinar - Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Presentation by Lini Wollenberg, Flagship Leader for CGIAR Research Program on Climate Change Agriculture Food Security Low-Emissions Development flagship. The presentation was part of the Webinar on Soil carbon in the Nationally Determined Contributions hosted by CCAFS, the German Ministry of Food and Agriculture, and the 4 Per Mille Initiative and held on Earth Day, 22 April 2020.